EKSPLORASI LEVEL INOVASI RESTORAN UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF DI KAWASAN PARIWISATA SANUR - Pinaria, Ni Wayan Chintia; Swandewi, Ni Kadek; Pranadewi, Putu Mira Astuti; Usadi, Made Pradnyan Permana (JUIMA : JURNAL ILMU MANAJEMEN, 2025)
This research aims to determine the level of restaurant innovation in the Sanur tourism area as part of an effort to build a competitive advantage. The population in this study includes restaurants serving Indonesian and Western food. The sample consists of restaurants with a Google Rating of 4.5-5 and over 1,500 reviews. Data was collected using two methods: web and social media observation, and direct observation. The analysis technique used is descriptive quantitative, which involves calculating the percentage of innovation and categorizing it into different levels of innovation. The research results show that the level of restaurant innovation in the Sanur tourism area varies, with one restaurant at a low level of innovation, six restaurants at a medium level, and one restaurant at a high level.  The average percentage of restaurant innovation implementation in the Sanur tourism area is 59%, placing these restaurants in the medium innovation level category. This research significantly advances our understanding of innovation within the hospitality and tourism sector by examining the innovative practices of restaurants in a leading tourist destination. The findings are highly valuable for various stakeholders. By implementing innovative strategies, restaurants can leverage these insights to enhance their competitive advantage.